PENGEMBANGAN GAWANG PANTUL LIPAT TERINTEGRASI UNTUK OPTIMALISASI PEMBELAJARAN SEPAKBOLA SISWA SEKOLAH DASAR - Muhammad Zaky Al Ghifary; Alit Rahmat (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to develop an integrated folding rebound goal based on a backward folding hinge articulation system as an adaptive two-in-one convergence sports facility for football learning in elementary schools. The Research and Development (R&D) method adopting ten procedural stages of the Borg and Gall model was utilized. Trial subjects involved material experts, media experts, and thirty sixth-grade elementary school students. Data collection used validation sheets, usability observations, and user response questionnaires. The results indicated that the folding rebound goal based on a frame-wedging mechanism and manual locking pin was highly feasible and practical for facilitating instant functional transition. The use of a plywood panel with a backing frame effectively reduced residual vibration, generating a stable ball rebound trajectory. In conclusion, this cost-effective product meets operational validity and reliability criteria as an alternative learning media to boost students' active learning time amidst school facility limitations.